Metformin modifies disparity in hepatocellular carcinoma incidence in men with type 2 diabetes but without chronic liver diseases. (16th April 2019) - Wang, Chen‐Pin; Kuhn, John; Shah, Dimpy P.; Schmidt, Susanne; Lam, Yui‐Wing F.; MacCarthy, Daniel; Tenner, Laura; Ramirez, Amelie G.
Abstract: Background: We assessed racial/ethnic disparity in hepatocellular carcinoma (HCC) incidence among men with type 2 diabetes (T2D) but without chronic liver diseases (CLD), and whether metformin use modified the disparity. Methods: Study cohort: the nationwide Veterans Administration Health Care System electronic medical records among 40‐89 years old men with T2D; without CLD, cancer, cardiovascular or renal diseases previously; insulin and thiazolidinedione naive. Logistic regression analyses compared HCC incidence between race/ethnicity groups under no metformin use adjusted for covariates and inverse propensity score weights (IPSW) for race/ethnicity. The generalizability technique integrated with IPSW was incorporated to compare covariates adjusted odds ratios (aOR) of HCC associated with metformin use among race/ethnicity groups. Results: Study cohort: N = 84 433; 79.47% non‐Hispanic white (NHW), 15.5% non‐Hispanic African American (NHAA), 5.03% Hispanics; 36.76% metformin users; follow‐up 6.10 ± 2.87 years; age 67.8 ± 9.8 years, HbA1c 6.57 ± 0.98%; 0.14% HCC cases. Under no metformin use, HCC incidence was lower for NHAA vs NHW (aOR = 0.60 [0.40‐0.92]), similar between NHW and Hispanics. Metformin was associated with reduced HCC risk: aOR = 0.57 (0.40‐0.81) for NHW; aOR = 0.35 (0.25‐0.47) for NHAA; aOR = 0.31 (0.22‐0.43) for Hispanics. Metformin dose >1000 mg/d was neutral for NHW; less effective for NHAA ( P  = 0.02); more effective for Hispanics ( P  = 0.002). Conclusions: In men with T2D but without CLD nor metformin use, HCC incidence was lower for NHAA compared to NHW or Hispanics; similar between NHW and Hispanics. Metformin use reduced HCC risk and modified the race/ethnicity disparity. Impact: Metformin's heterogeneous HCC prevention effect elucidates potential interventions to modify HCC disparity in patients with T2D. Abstract : Metformin's heterogeneous effect on hepatocellular carcinoma (HCC) prevention elucidates potential intervention strategies to modify HCC disparity in patients with type 2 diabetes.